Hijab gaya hidup wanita Islam Murtadha Muthahhari ; penerjemah Agus Efendi, Alwiyah Abdurrahman ; penyunting, Ilyas Hasan - Muthahhari, Murtadha; Efendi, Agus; Abdurrahman, Alwiyah; Hasan, Ilyas (Mizan, 1990)
192 hlm 18 cm